Clinical and radiologic manifestations of Mycoplasma pneumoniae infection in children - Ocak, Melike; Öz, Fatma Nur; Çınar, Hasibe Gökçe; Tanır, Gönül (The Turkish Journal of Pediatrics, 2022)
Background. Mycoplasma pneumoniae (MP) is one of the most important etiological agents of communityacquired pneumonia in children. Methods. The medical records of children with an MP infection between 2008 and 2015 were reviewed for their clinical, laboratory radiological features. Results. This study included 244 patients (male 57.4%) with a median age of 80.5 months (IQR, 46.5-120 months). A total of 78 (32%) patients were < 5 years old, and 166 (68%) were ≥ 5 years old. The most common complaints before admission to the hospital were cough (84.8%), fever (57.4%), and weakness (18.9%). In the < 5 years old age group, oxygen saturation was lower, and tachypnea was more common than in the ≥ 5 years old age group (p=0.02 and p=0.05, respectively). Similarly, the physical findings such as the prolonged expiration, presence of retractions, and rhonchi were more frequent in the < 5 years old age group (p=0.001, p=0.000, p=0.02, respectively). Extrapulmonary manifestations were present in 45 (18.4%) patients, and skin involvement was the most common one (7.7%). Two hundred-thirty-eight (97.5%) patients had chest radiographs, and 45 (18.4%) had normal radiography. The most common radiological involvement was peribronchial infiltration (n=70, 28.7%). Of the patients, 147 (60.2%) were hospitalized, and 97 (39.7%) were followed up as outpatients. It was determined that 156 (63.9%) patients had commenced macrolide empirically, and 61 (25%) patients were treated with positive serology results. Conclusions. The prolonged fever, cough and expiration time, wheezing and rhonchi in younger children, and segmental-lober consolidation in chest radiography could be clues for MP infection. Further studies in different age groups can facilitate an understanding of MP infection`s epidemic characteristics and clinical features that will provide early diagnosis and appropriate treatment.
Keywords: Mycoplasma pneumoniae; children; infection; radiograph